HSP60: Issues and Insights on Its Therapeutic Use as an Immunoregulatory Agent - Coelho, Veronica; Faria, Ana Maria C. (Frontiers in Immunology, 2012)
Heat shock proteins 60 (HSP60) is one of the most well studied member of the HSP family. Although found to be a target self antigen in pathological autoimmunity and HSP60-reactive T and B cells are part of immune responses in several infectious diseases, there is consistent experimental evidence that HSP60 displays dominant immunoregulatory properties. There are a series of reports on animal models showing that the administration of HSP60 can modulate inflammatory diseases. However, HSP60 has both immune-regulatory and inflammatory properties placing it as an essentially homeostatic antigen, but with potentially harmful effects as well. There have been a series of reports on the successful use of HSP60 and its peptides as immune-modulatory agent for several models of autoimmune diseases and in some clinical trials as well. We believe that the potential risks of HSP60 as a therapeutic agent can be controlled by addressing important factors determining its effects. These factors would be route of administration, appropriate peptides, time point of administration in the course of the disease, and possible association with other modulatory agents.